2004
DOI: 10.1183/09031936.04.00140603
|View full text |Cite
|
Sign up to set email alerts
|

Home respiratory polygraphy for diagnosis of sleep-disordered breathing in heart failure

Abstract: The present study assessed the usefulness of home cardiorespiratory polygraphy as an alternative to overnight polysomnography for the diagnosis of sleepdisordered breathing in heart failure.A total of 75 patients with chronic stable heart failure due to systolic dysfunction (left ventricular ejection fraction f45%) underwent polysomnography at the Virgen del Rocio Hospital and cardiorespiratory polygraphy at home. The two studies were performed in random order and within 30 days. The accuracy of polygraphical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 31 publications
(38 reference statements)
2
48
1
6
Order By: Relevance
“…However, different studies investigating the ability of polygraphy to detect sleep-disordered breathing showed a high diagnostic accuracy of the portable recording devices [42][43][44]. It is unlikely that the additional information on sleep stages given by polysomnography would profoundly modify the results.…”
Section: Limitationsmentioning
confidence: 99%
“…However, different studies investigating the ability of polygraphy to detect sleep-disordered breathing showed a high diagnostic accuracy of the portable recording devices [42][43][44]. It is unlikely that the additional information on sleep stages given by polysomnography would profoundly modify the results.…”
Section: Limitationsmentioning
confidence: 99%
“…[46][47][48]52,55,81,88,89,98,104 In addition, 7 of 14 inlaboratory studies showed a decline in sensitivity and an increase in specificity, and 2 studies showed an increase in area under the ROC curve. 47,48,51,52,58,[61][62][63][65][66][67][69][70][71] We found no significant difference in baseline characteristics between the 2 groups of patients in all 8 studies that reported disease management after the diagnosis by either test.…”
Section: Diagnostic Accuracy Of Sleep Testsmentioning
confidence: 99%
“…The performance of SM in detecting and screening SDB in this HF cohort was comparable to other forms of portable/home contact screening devices 14, 15, 16, 17, 18, 19. However, most of these studies only included patients without HF.…”
Section: Discussionmentioning
confidence: 74%
“…PMs are usually used as an initial diagnostic or screening tool and in selected patients, if the test results are positive, can be used to recommend treatment, while ruling out additional testing if results were negative 16. PMs can be used on an unattended basis, and several studies have reported a high diagnostic accuracy of up to 90% in detecting SDB 17, 18, 19, 20, 21. High study failure rates because of their complex unattended design can, however, result in the need for repeated studies 16.…”
Section: Introductionmentioning
confidence: 99%